The Effect of Leverage Towards Dividend Policy with Creative Accounting as The Mediation Variable - Kurniawan Dwi Pradipta; Susi Handayani (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2020)
The purpose of this study was to examine the effect of the leverage ratio on dividend policy mediated by creative accounting. This research is based on the existence of a dividend policy which is influenced by various factors, including debt to equity ratio. A high debt-to-equity ratio indicates a high risk because high corporate debt will have an impact on high-interest costs and debt burdens that must be paid. This will result in a small number of dividends being distributed to investors. Meanwhile, investors are very interested in the high dividend payout and receive cash according to the Bird-in-Hand Theory. This study will examine registered banking companies in Indonesia from 2014 to 2018. The sample was taken by a purposive random sampling technique. The independent variable used in this research is leverage measured with debt-to-equity ratio (DER). The dependent variable used in this research is dividend policy measured with dividend payout ratio (DPR) and the mediation variable used in this research is creative accounting measured with discretionary accrual (DA). The results in this research indicate that leverage has a negative effect on creative accounting and also creative accounting cannot mediate a relationship between leverage towards dividend policy.